Reasons behind Delayed Orchidopexy at Our Tertiary Centre - Gupta, Dr. Vinita Chaturv, Dr. Sunil Kumar Mehra, Dr. Dinesh Kumar Barolia, Dr. Arun Kumar (International Journal of Innovative Research in Medical Science, 2018)
This study was conducted in children of undescended testes at tertiary centre. Purpose of this study was to evaluate the reasons behind delayed orchidopexy at our tertiary centre. This study was conducted in 300 male children of undescended testes, which were operated at our centre.